Study and Analysis of Some Real Life Applications of Exponential Function - Mahato, Suraj Kumar; Sahani, Suresh Kumar; Sahani, Kameshwar; Sah, Binod Kumar; Karna, Santosh Kumar (Lembaga Yasin AlSys, 2024)
The exponential function as a mathematical concept plays an important role in the Corpus of mathematical knowledge, but unfortunately Students have problems grasping it. Paper exposes examples of exponential function application in a real-world (life).One of the most prevalent applications of exponential functions Involves growth and decay models. Exponential growth and decay show up in a host of natural applications. From population growth and continuously compounded Interest to radioactive decay and Newton's law of cooling, exponential functions are ubiquitous in nature. In this section, we examine exponential grown and decay in the context of some of the applications. In the preceding section, we examined a population growth problem in which the population grew at a fixed percentage each year. In that case, we found that the population can be described by an exponential function. A similar analysis will show that any process in which a quantity grows by a fixed percentage each year (or each day, hour etc.) can be modeled by an exponential function. Compound Interest is a good example of such a process. Other applications of exponential function are bacterial growth, bacterial decay, population decline, are obtained in this project.